ANALYSIS DIALECT VARIATION ON SOCIAL INTERACTION IN THE INDEPENDET STUDENT EXCHANGE PROGRAM - Muhammad Saddam; Sukma, Arya Nara; Afrianto, Wiutami Danesha; Rahmah, Khilda Umi; Nargis, Nargis (Media Inovasi Pendidikan dan Publikasi, 2025)
This study analyzes dialect variation on social interactions among students participating in the Independent Student Exchange Program (PMM) under the Merdeka Belajar Kampus Merdeka (MBKM) initiative. Using a qualitative phenomenological approach, data were obtained through interviews and Likert-scale questionnaires. The results showed that dialect variation significantly affected social interactions, with 80% of students perceiving differences in speaking style and 60% acknowledging a moderate impact on their interactions. Despite minor challenges in understanding dialects, students recognized the importance of dialect awareness, as reflected in an average score of 4.2 out of 5 on the Likert scale. The findings highlight the dual role of dialect variation as both a challenge and an opportunity for cultural exchange and social cohesion. Recommendations include incorporating dialect awareness sessions into program orientations to enhance intercultural communication skills.